Can gold hedge the risk of fear sentiments? - Su, Chi-Wei; Liu, Yiru; Chang, Tsangyao; Umar, Muhammad (Technological and Economic Development of Economy, 2023)
This paper investigates the interaction between fear sentiments and gold price (GP) by utilising the full-sample and sub-sample rolling-window bootstrap causality tests. It can be observed that GP can hedge the risk of fear sentiments in a certain period. The result supports the inter-temporal capital asset pricing model, which demonstrates that the increase in fear sentiments can promote the rise in gold prices. Due to excessive panic, fear sentiments also have negative effects on GP. In contrast, GP positively impacts fear sentiments, which manifests that market sentiment can be forecasted based on changes in the gold market. In addition, the negative influences from GP to fear sentiments indicate there are diversified assets that can be alternatives to gold. In the complicated international environment and volatile market sentiments, investors can benefit by optimising their asset portfolio. The governments can mitigate the adverse effects of large fluctuations in both markets by grasping the movement of gold and fear sentiments.First published online 16 December 2022